2017
DOI: 10.1123/japa.2016-0106
|View full text |Cite
|
Sign up to set email alerts
|

Increased Thermoregulatory Strain When Wearing an Upper Body Compression Garment During Moderate Exercise in Trained Older Adults

Abstract: The efficacy of the use of an upper body compression garment (UBCG) as an ergogenic aid to reduce thermoregulatory strain in older adults remains unknown. The aim of this study was to evaluate the effects of UBCG on thermoregulatory, cardiorespiratory, and perceptual responses during cycling in a temperate environment (~25 °C, 66% rh) in trained older adults. Twelve cyclists aged 66 ± 2 years performed an intermittent 1-hr cycling trial at 50% of the peak power output followed by 10 min of passive recovery. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(24 citation statements)
references
References 0 publications
2
19
1
Order By: Relevance
“…No studies reported negative effects of compression on blood pressure, cardiac output or stroke volume. Compression literature investigating changes in mean arterial pressure [109,176,178,183] and total vascular conductance [176] has reported no effect of compression. Additionally, there is mixed evidence on the effects of compression garments on other cardiovascular measures.…”
Section: Cardiovascular and Haemodynamic Outcomesmentioning
confidence: 99%
See 4 more Smart Citations
“…No studies reported negative effects of compression on blood pressure, cardiac output or stroke volume. Compression literature investigating changes in mean arterial pressure [109,176,178,183] and total vascular conductance [176] has reported no effect of compression. Additionally, there is mixed evidence on the effects of compression garments on other cardiovascular measures.…”
Section: Cardiovascular and Haemodynamic Outcomesmentioning
confidence: 99%
“…Thirty-seven studies investigated cardiorespiratory outcomes related to compression garments (refer to Table S5 of the ESM). The majority of studies involved running (n = 23, 62%) [7,12,17,28,47,52,64,102,115,119,127,132,133,135,143,145,147,162,164,166,177,180,181] or cycling (n = 10, 27%) [5,22,100,109,123,165,171,178,183,185] as the primary form of exercise. However, activities relating to alpine skiing (i.e.…”
Section: Cardiorespiratorymentioning
confidence: 99%
See 3 more Smart Citations